Why Freeter and NEET are Misunderstood: Recognizing the New Precarious Conditions of Japanese Youth - Akio Inui (Social Work & Society, 2005)
In developed countries, the transition from school to work has radically changed over the past two decades. It has become prolonged, complicated and individualized (Bynner et al., 1997; Walther et al., 2004). Young people used to transition directly from school to stable employment, or with a very short unemployed period. In many European countries, this situation has been changing since the eighties: overall youth unemployment has increased, and many young people experience long periods of unemployment, government training schemes and part-time or temporary jobs. In Japan, this change has taken a decade later to appear, becoming prevalent by the late nineties (Inui, 2003). The transiting process has become not only precarious for young people, but also difficult for society to precisely understand the risks and problems. Traditionally, we have been able to recognize young people's situation by a simple category: in education, employed, in training or unemployed. However, these categories no longer accurately represent young people's state. In Japan, most young people used to move from school directly to full-time employment through the new graduate recruitment system (Inui, 1993). Therefore, in official statistics such as the School Basic Survey, 'employed' includes only those who are in regular employment, while those who are in part-time or temporary work are covered by the categories 'jobless' and 'others'. However, with the increase in non-full-time jobs in the nineties, these categories have become less useful for describing the actual employment conditions of young people. Indeed, this is why, in the late of nineties, the Japanese Ministry of Education changed the category name from 'jobless' to 'others'.